2019
DOI: 10.1248/cpb.c19-00508
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Bitter Taste Sensor Response and Physicochemical Properties of 47 Pediatric Medicines and Their Biopharmaceutics Classification

Abstract: The purpose of this study was to investigate the relationship between response to the bitterness taste sensor and physicochemical parameters of 47 pediatric medicines and to classify these medicines according to the biopharmaceutics classification system (BCS). Forty-seven bitter compounds, most of which were on the WHO model list of essential medicines for children (March 2017), were used in the study. Solutions (0.1 mM) were evaluated by an artificial taste sensor using membranes sensitive to bitterness. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…In a previous study, Uchida et al reported that acidic beverages should be avoided when taking powder formulations of macrolide antibiotics because the acidic beverage was found to produce a strongly bitter taste, as stated in the information sheet for Clarith ® dry syrup. 22,23) Because azithromycin also belongs to the macrolide antibiotic class of medicines, orange juice might increase the bitterness of azithromycin with the same mechanism. In our study, the sport drink (pH 3.5) and orange juice (pH 3.6) were mild acidic solutions, the other drinks were in a neutral range (pH = 6.0-7.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Uchida et al reported that acidic beverages should be avoided when taking powder formulations of macrolide antibiotics because the acidic beverage was found to produce a strongly bitter taste, as stated in the information sheet for Clarith ® dry syrup. 22,23) Because azithromycin also belongs to the macrolide antibiotic class of medicines, orange juice might increase the bitterness of azithromycin with the same mechanism. In our study, the sport drink (pH 3.5) and orange juice (pH 3.6) were mild acidic solutions, the other drinks were in a neutral range (pH = 6.0-7.5).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, some studies were reported to evaluate the bitterness of some medicines quantitatively using a taste sensor. [21][22][23][24][25] The research of taste sensors has made a breakthrough by achieving high selectivity for each taste, especially bitterness. For example, Tanigake et al evaluated the bitterness intensity of clarithromycin with some beverages by a taste sensor.…”
Section: Resultsmentioning
confidence: 99%
“…The field of in vitro taste assessment is continually evolving. For the Insent etongue, a new taste sensor BT0 has been introduced but was not available at the time of our study; it was designed to be more useful for evaluating the bitterness of hydrochloride salt compounds [34]. Moreover, in recent years, bioelectronic tongues (BioETs), integrating biological materials and various types of transducers, have been proposed to bridge this gap between chemical sensors and biological taste [42].…”
Section: Discussionmentioning
confidence: 99%
“…In exploring the relationship between the physicochemical properties of paediatric drugs of various Biopharmaceutical Classification System (BCS) class drugs and their bitter baste sensor response, the dose number (D0) was used by Haraguchi et al [34]. This took not only the solubility of the drug but also the highest dose taken with a 250 mL glass of water in account.…”
Section: Determination Of Taste Indexmentioning
confidence: 99%
“…Taste sensor SA402B (Intelligent Sensor Technology Inc., Atsugi, Japan) was used to measure the electric potential of the sample solutions (at the same con-centrations as those used in human gustatory sensation testing) in order to predict their taste. Sensor AC0, developed specifically to detect the bitterness of basic substances [14] [15] [16], was used in these experiments. The taste sensor measurements were performed to evaluate bitterness intensity for amlodipine besilate [6], solifenacin succinate [7], H 1 -receptor antagonists [9] and topiramate [17] as described in previous articles.…”
Section: Taste Sensor Measurements Of Dry Syrups Mixed With Beveragesmentioning
confidence: 99%